2002
DOI: 10.1083/jcb200108056
|View full text |Cite
|
Sign up to set email alerts
|

The trefoil factor 1 participates in gastrointestinal cell differentiation by delaying G1-S phase transition and reducing apoptosis

Abstract: Trefoil factor (TFF)1 is synthesized and secreted by the normal stomach mucosa and by the gastrointestinal cells of injured tissues. The link between mouse TFF1 inactivation and the fully penetrant antropyloric tumor phenotype prompted the classification of TFF1 as a gastric tumor suppressor gene. Accordingly, altered expression, deletion, and/or mutations of the TFF1 gene are frequently observed in human gastric carcinomas. The present study was undertaken to address the nature of the cellular and molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(130 citation statements)
references
References 54 publications
7
114
1
7
Order By: Relevance
“…Previous studies have demonstrated that both TFF1 and Cdc25A are involved in the regulation of cell proliferation and apoptosis (Bossenmeyer-Pourie et al, 2002;Kang et al, 2004;Leisser et al, 2004). Consistent with this, we next examined the impact of TFF1 ectopic expression on cell survival in TFF1-transformed colon epithelial cells, using the potent apoptosis inducer thapsigargin (TG).…”
Section: Increased Cell Survival In Tff1-transformed Colon Epithelialsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have demonstrated that both TFF1 and Cdc25A are involved in the regulation of cell proliferation and apoptosis (Bossenmeyer-Pourie et al, 2002;Kang et al, 2004;Leisser et al, 2004). Consistent with this, we next examined the impact of TFF1 ectopic expression on cell survival in TFF1-transformed colon epithelial cells, using the potent apoptosis inducer thapsigargin (TG).…”
Section: Increased Cell Survival In Tff1-transformed Colon Epithelialsupporting
confidence: 54%
“…The transforming functions of TFFs in the digestive tract and other solid tumors are supported by their positive actions on tumor cell invasion, angiogenesis and survival (Emami et al, 2001;Bossenmeyer-Pourie et al, 2002;Rodrigues et al, 2003a, b). To our knowledge, the status and biological significance of TFF1 at the adenoma and carcinoma transitions in the intestine has not been elucidated.…”
Section: Induction Of Tff1 At the Adenoma And Carcinoma Transitionsmentioning
confidence: 99%
“…TFF1 delays the transition from G1 to the S-phase in the cell cycle, thus regulating tumor inhibition, mucosal protection, cell apoptosis and differentiation (30). The expression of TFF1 in inflammation and malignant tumors indicates the status of prognosis and is significantly negatively correlated with the therapeutic effect of hormone therapy (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent reports support the notion that Tff1 may be a candidate tumor suppressor gene that may be involved in development and/or progression of human gastric cancers. 6,7,9 The Tff1 knockout (Ϫ/Ϫ) mouse model was first reported in 1996 as a model for spontaneous development of intestinal-type gastric dysplasia and cancer, similar to human disease. 10 Thus, the Tff1Ϫ/Ϫ mouse model provides a window to look into molecular alterations that are associated with precancerous lesions and understand the development of gastric cancers.…”
mentioning
confidence: 99%